Paraíso de Labriegos” exploraciones metodológicas desde una apuesta virtual de la práctica pedagógica investigativa III con el grupo de adulto mayor en EAAEA - Romero Tocarruncho, Gabriela Alejandra (Universidad Antonio Nariño, 2021)
A systematization of the experience of the investigative pedagogical practice III at the Antonio Nariño University (UAN) with the Senior Adult group at the Open School of Art and Art Education (EAAEA), which in the midst of the pandemic bet on the implementation of a 6-phase methodology, which aims to build knowledge from the methodological exploration for the application in the virtual classroom, from the teaching of dance in the Andean region and its dance and cultural manifestation, focused on the choreographic groups and games of the Carnival of Negros and Blancos de Pasto Nariño from the Colombian territory, with a population of elderly people in a training process and reassembly of the work "Paraíso de Labriegos", outside the common learning environment.